Early C-reactive protein reduction predicts survival in real-world extensive-stage small cell lung cancer treated with first-line adebrelimab-based immunotherapy - Wang, Jian; Zhang, Xueli; Gao, Qijia; Chen, Jianxin (Frontiers in Oncology, 2025)
BackgroundExtensive-stage small cell lung cancer (ES-SCLC) remains an aggressive malignancy with limited biomarkers for predicting outcomes in real-world settings. While baseline systemic inflammation correlates with prognosis, the role of longitudinal inflammation dynamics during PD-L1 inhibitor-based therapy is unexplored. This study investigated whether early changes in systemic inflammation markers, particularly C-reactive protein (CRP), predict clinical efficacy in ES-SCLC patients receiving first-line adebrelimab plus chemotherapy.MethodsIn this retrospective, single-center study, 35 ES-SCLC patients (median age: 72 years) treated with adebrelimab plus platinum-etoposide or platinum-irinotecan chemotherapy were analyzed. Ten systemic inflammation markers (NLR, PLR, LMR, PAR, SII, NPR, CAR, CLR, CRP, LDH) were assessed at baseline and after 2 months of therapy. Inflammatory trends were quantified as the ratio of 2-month to baseline values. Associations between inflammation dynamics and survival (OS from 2 months, OS2) or radiologic response (RECIST 1.1) were evaluated using Kaplan-Meier analysis, Cox regression, and Spearman’s correlation.ResultsThe cohort showed robust real-world efficacy (median OS: 15.0 months; ORR: 62.8%). Among ten inflammation markers analyzed, only CRP dynamics were significantly associated with OS in univariate analysis. Patients achieving CRP reduction (trend ratio <1) at 2 months had significantly longer median OS (16.2 months) versus those without reduction (8.1 months; HR = 3.492, 95% CI:1.239–9.847, P = 0.011). No other inflammatory trend correlated with OS. Inflammation dynamics (including CRP) showed no association with best overall response or tumor regression (P>0.05 for all markers).ConclusionEarly reduction in CRP levels during adebrelimab-based chemoimmunotherapy is an potentially predictor of improved survival in ES-SCLC, despite dissociation from initial radiologic response. This suggests that CRP kinetics could serve as a practical, real-world biomarker for prognostication and early efficacy assessment in ES-SCLC. Prospective validation in larger cohorts is essential to confirm these findings.